2021
DOI: 10.1016/j.abrep.2021.100362
|View full text |Cite
|
Sign up to set email alerts
|

Why should we ask binge drinkers if they smoke cannabis? Additive effect of alcohol and cannabis use on college students’ neuropsychological performance

Abstract: Highlights This study focused on combined binge drinking and cannabis use in college students. Cannabis use and binge drinking had an additive effect on cognition. This consumption pattern contributed to memory and executive impairments. Binge drinkers had a heterogeneous cognitive profile regardless of cannabis use. Cannabis use should be assessed in binge drinkers to adapt prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This finding clearly indicates that binge drinking should not be considered a recreational pattern and could shed light on how short-term binge drinking already affects academic performance ( Kuntsche et al, 2017 , Páramo et al, 2020 , Patte et al, 2017 ). In a similar vein, Deniel et al (2021) highlight the harmful additive effect of cannabis use and binge drinking on cognition. The authors observed not only poorer neuropsychological performance among binge drinkers in comparison with light drinkers (whether they used cannabis or not), but also specific impairments in flexibility, episodic memory, and working memory among binge drinkers who used cannabis.…”
Section: Summary Of the Current Special Issuementioning
confidence: 93%
See 1 more Smart Citation
“…This finding clearly indicates that binge drinking should not be considered a recreational pattern and could shed light on how short-term binge drinking already affects academic performance ( Kuntsche et al, 2017 , Páramo et al, 2020 , Patte et al, 2017 ). In a similar vein, Deniel et al (2021) highlight the harmful additive effect of cannabis use and binge drinking on cognition. The authors observed not only poorer neuropsychological performance among binge drinkers in comparison with light drinkers (whether they used cannabis or not), but also specific impairments in flexibility, episodic memory, and working memory among binge drinkers who used cannabis.…”
Section: Summary Of the Current Special Issuementioning
confidence: 93%
“…This Special Issue gathers 11 original research and review articles that address different types of binge behaviors: binge drinking ( Deniel et al, 2021 , Gierski et al, 2020 , Herman et al, 2020 , Mange et al, 2021 , Werle et al, 2021 ), binge eating ( Prunell-Castañé et al, 2021 , Werle et al, 2021 ), binge watching ( Cordeiro et al, 2021 , Ort et al, 2021 , Rubenking and Bracken, 2021 , Werle et al, 2021 ), and binge-porn consumption (i.e., hypersexuality and problematic pornography use; Castro-Calvo et al, 2021 , Koós et al, 2021 ). These articles primarily consist of empirical studies that build on self-report questionnaires, but a few rely on behavioral assessments, ecological approaches (i.e., sampling experiences), or literature reviews.…”
Section: Summary Of the Current Special Issuementioning
confidence: 99%
“…Previous studies have indicated that the simultaneous use of alcohol and cannabis amplifies the likelihood of experiencing severe alcohol-related outcomes, such as blackouts ( Davis et al, 2021 ; Jackson et al, 2020 ). In addition, Deniel et al (2021) reported that the consumption pattern of cannabis use and binge drinking contributes to memory and executive impairments among college students. It is important to recognize that blackouts can also serve as a moderator in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of other substances (such as cannabis) on suicidality remains largely unknown because of the conflicting evidence [ 15 , 16 ], literature suggests that the number of substances used is more important in predicting suicidality than the type of substances used [ 17 ]. It is generally known that simultaneous use of both cannabis and alcohol has additive harmful effects than using either substance on neuropsychological functioning [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%